Critical Review on Action of Shaddarana Choorna in Koshtam (International Journal of Ayurveda and Pharma Research, 2024)
Gastrointestinal disorder are nowadays very common in population because of change in their life style, food habits, mental stress. Koshta is considered as very important, it is the seat of agni and dosha. Agni plays an important role in GIT and it is the main factor for metabolism. If Agni get hampered due to formation of ama in amashaya and leads to various disease. Shaddharana choornam act on koshta especially in amashaya by improving agni by reducing ama and make vata anulomana. The reference of shaddharana choorna in Susrutha samhita in vatavyadhi chikitsa.